2016
DOI: 10.2217/imt-2016-0052
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Anti-Oncodriver Th1 Responses with Dendritic Cell Vaccines in HER2/ neu -Positive Breast Cancer: Progress and Potential

Abstract: HER2/neu is expressed in the majority of in situ breast cancers, but maintained in 20–30% of invasive breast cancer (IBC). During breast tumorigenesis, there is a progressive loss of anti-HER2 CD4pos Th1 (anti-HER2Th1) from benign to ductal carcinoma in situ, with almost complete loss in IBC. This anti-HER2Th1 response can predict response to neoadjuvant therapy, risk of recurrence and disease-free survival. Vaccines consisting of HER2-pulsed type I polarized dendritic cells (DC1) administered during ductal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 89 publications
0
21
0
Order By: Relevance
“…It has been revealed that infiltrating T cells and production of cytokines into tumor tissue is associated with improved clinical outcome in numerous types of cancers [ 7 , 10 ]. More specifically, T helper (Th) cells play central roles in the development of immune responses [ 11 ]. Recent studies have indicated that the balance between different CD4 + Th subsets (Th1, Th2, Th17, and Treg) is important in anti-tumor immunity, and perhaps, in the process of tumor progression [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that infiltrating T cells and production of cytokines into tumor tissue is associated with improved clinical outcome in numerous types of cancers [ 7 , 10 ]. More specifically, T helper (Th) cells play central roles in the development of immune responses [ 11 ]. Recent studies have indicated that the balance between different CD4 + Th subsets (Th1, Th2, Th17, and Treg) is important in anti-tumor immunity, and perhaps, in the process of tumor progression [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The huge chapter of the immune adjuvants of endogen or exogen origin has to be deepened and may represent a major area of interest for the future. Immunotherapy is currently being tested for solid and hematological cancer from early to metastatic stage, with protocols involving it with an anxillary role or as a protagonist in cancer fighting for an increasing number of patients, eluding escaping variants ( 14 , 49 , 53 ). To let immunotherapy be the wished revolution in cancer therapy including BC, bioinformatics, drug design/pharmacology, molecular biology, data analysis, clinical science, and medical imaging will need to share an emerging mentality.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, T-cell stimulation aims to induce the activity of both T-helper and natural killer T cells. Strategies to increase Th1- (CD4 + ) and cytotoxic T-lymphocytes- (CTLs, CD8 + ) dependent immunity and to suppress Th1–Treg joined responses are currently being tested ( 14 ). This review will focus on the new perspectives for the use of BC vaccines ( 15 , 16 ), considering the ongoing clinical trials and the possible future perspectives to combine immunomodulation with other BC therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Czerniecki et al showed anti-HER2 CD4 + Th1 immunity to be a relevant component of HER2 + therapy, as loss of CD4 + Th1 responses correlated with poor prognosis and treatment responses 15 . The administration of a class II HER2 peptide-pulsed Type I polarized DC1 vaccine was shown to induce a strong anti-HER2 CD4 + Th1 response, with a pathologic complete response rate (pCR) among HER2 + ductal carcinoma in situ (DCIS) patients [69][70][71] .…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%